2007
DOI: 10.1111/j.1479-828x.2007.00784.x
|View full text |Cite
|
Sign up to set email alerts
|

Employee entitlements during pregnancy and maternal psychological well‐being

Abstract: Workplace adversity during pregnancy is associated with poorer maternal psychological well-being. Workplace conditions and entitlements are salient factors for consideration in assessments of antenatal psychosocial well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…The effect of job stress is consistent with what has been shown in previous research-lower schedule autonomy [18,19,38], psychological demands [17], and lack of perceived control [17], all components of a stressful work environment, negatively influence the mental health of women with young children. The results from our study contradict findings from past studies that found no association between working from home and depressive symptoms [18].…”
Section: Discussionsupporting
confidence: 89%
“…The effect of job stress is consistent with what has been shown in previous research-lower schedule autonomy [18,19,38], psychological demands [17], and lack of perceived control [17], all components of a stressful work environment, negatively influence the mental health of women with young children. The results from our study contradict findings from past studies that found no association between working from home and depressive symptoms [18].…”
Section: Discussionsupporting
confidence: 89%
“…Lastly, causal inferences should be made cautiously as the questionnaire did not collect information on the temporal sequence between prenatal psychological distress and associated characteristics. The present study highlights the link between social and economical vulnerabilities and the occurrence of prenatal psychological distress, in accordance with previous studies [10,22,36,43,44]. Mothers using tobacco or alcohol were also more likely to present with poor prenatal mental health, as also reported by several other studies [15,19,34,36].…”
Section: Discussionsupporting
confidence: 93%
“…29 Almost half the respondents endorsed a reduction in sexual violence (48%), but structural factors were also regarded as important agents of reproductive autonomy: guaranteed paid maternity leave (70%) and flexible familyfriendly work conditions for parents (55%), improved job security (50%) and pay equity for women (50%). Indeed there is a social gradient in access to employee entitlements for pregnant women 30 and it could be argued that, if these entitlements were universally available, fewer pregnancies might be regarded as 'unintended' .…”
Section: Discussionmentioning
confidence: 99%